Development of local function. Issue 8 (17th November 2022) - Hadi, Mustafa Hasan; Hadi, Huda Amer; Al-Swidi, Luay A.
Abstract: In this paper we develop the concept of local function via - ω open. We also study the densities and their properties with respect to - ω open in the ideal topological spaces. We also defined - I ω hyper, - I ω resolvable and - ω condense by expanding the definition of ideal topological space and associating it with set - ω open.